Pengembangan Helpdesk Ticketing System berbasis Website dengan menggunakan metode SDLC, XP, dan Scrum - Mangapul Siahaan; Kelvin (STMIK Budi Darma, 2023)
The current rapid advancement of information technology is closely tied to the growing demand for information. The web has evolved into a tool that not only provides information but also processes it. Utilizing web technology for information processing has turned the web into a dynamic information medium. There are numerous possibilities with web applications, such as developing a Helpdesk Ticketing System for companies or institutions to establish a more effective and efficient issue reporting system. The increasing number of internally reported issues has made tracking all reported problems more challenging. The result of this research is the system prototype has been successfully built. The built system can operate as expected by system users, which is demonstrated by the results of testing using the black box testing method. The outcomes of this research is to identify the application development model that can expedite and enhance the development process using three methods, namely Software Development Life Cycle (SDLC), Extreme Programming (XP), and Scrum. The utilization of the XP method approach by the researcher in building the helpdesk ticketing system has proven to be highly effective in accelerating system development